Content Analysis of Library Websites of the Centre with Potential for Excellence in Particular Area (CPEPA) Universities - Roy, Sanraj; Bhattacharyya Sahu, Nivedita (DESIDOC Journal of Library & Information Technology, 2024)
Libraries are taking a quint essential position in accumulating and disseminating fact offerings via library websites. The websites portray the library collection, library services, social networking sites, and web 2.0 tools used in the libraries. This study aims to evaluate the seventeen library website features of the Centre with Potential for Excellence in Particular Area (CPEPA) universities by identifying them through previous literature and consulting the checklist. Individual websites of the CPEPA Universities are consulted for the study. It helps users collect more information about those institutions. It significantly corresponds with the aspects of website assessment on the service, innovative solutions, multi-media options, web 2.0, e-resources and e-databases and platforms provided for easy information retrieval by their users and useful social networking plug-ins. The study reveals that there are seventeen Universities under the CPEPA scheme, the library websites mention about its mission, and vision statement. Sixteen out of seventeen universities provide information on library rules, library staff, library sections, and important web links, working hours & holiday lists. Most of the libraries have independent library website which is linked with University URL. All library websites except Jai Narain Vyas University provide e-journal and e-book links directly on the website. The libraries don’t have a uniform library collection. Only 15 universities reflect the information of LMS and institutional repository details. Only Devi Ahilya University and Himachal Pradesh University libraries depict materials for blind users. Annamalai University and Guru Nanak Dev University libraries have coins in their collection. Lending, Inter-library loan, SDI and CAS, reference service and web 2.0 services are most common services provided by all the libraries. Seven university websites have bi-lingual interfaces. Only 6 universities provide keyword search facilities. Online book reservation facility is available only in University of Allahabad library. The study concludes that well designed library websites are very essential for today’s digital environment and for enabling a 24*7 access to library resources. All the libraries under CPEPA Universities have not yet developed their websites full-fledged and needs more to be more comprehensive.